Tannin alleviated reproductive dysfunction in pregnant ewes infected with Haemonchus contortus - Li, Xin; Xiang, Hai; Liang, Rong; Han, Xinyu; Zhong, Rongzhen; Liu, Hongyu; Fang, Yi (Frontiers in Veterinary Science, 2025)
IntroductionHaemonchus contortus (H. contortus) infection has a significant impact on the health of pregnant ewes and adversely affects fetal development, highlighting the critical need for a non-toxic feed additive as an alternative and sustainable control strategy. Tannin is a kind of polyphenol compound, which has certain antiparasitic. The objective of this study was to evaluate the impact of dietary tannin supplementation on fecal egg count (FEC), packed cell volume (PCV), complete blood count (CBC), hormone levels, inflammatory markers, placental inflammation, and fetal growth and development in pregnant ewes infected with H. contortus.MethodsHulunbuir ewes were randomly divided into three groups: control group (CON), gastrointestinal nematode infection group (GIN), and tannin group, which was infected by H. contortus with tannin feeding therapy (TAN). After artificial insemination was completed, and the ewes were confirmed for pregnancy and infection; stools were collected for FEC, and blood samples were collected for PCV and CBC, hormonal, and inflammation levels. The mRNA levels of hypothalamic–pituitary–ovarian axis-related hormone receptors and placental tissue inflammation genes were detected by quantitative reverse transcription polymerase chain reaction (RT-qPCR). Finally, fetal weights were measured, and fetal ovarian tissue samples were taken for transcriptomic analysis.ResultsThe results showed that tannins increased the levels of gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), estrogen (E2), progesterone (P4), human chorionic gonadotropin (hCG), red blood cell (RBC) counts, packed cell volume (PCV), and mRNA levels of gonadotropic axis receptors in pregnant ewes infected with H. contortus (p < 0.05). In addition, tannin reduced fecal egg count (FEC), leukocyte counts, and mRNA levels of inflammatory markers (p < 0.05). In addition, fetal ovarian sequencing further showed that tannin may alleviate the delay in fetal growth and development induced by H. contortus infection (p < 0.05).ConclusionIn summary, tannins have anthelmintic effects, restore reproductive hormone levels in pregnant ewes, reduce inflammation levels, and alleviate fetal growth retardation caused by H. contortus infection. Therefore, tannin is a suitable potential alternative to antibiotics as a feed additive.